Economic analysis of two processes for biodiesel production. Issue 7 (2nd April 2016) - Li, Jiaqi; Chen, Xiaohui; Xu, Chengzhi; Wei, Kemei
ABSTRACT: In this study, two continuous processes for biodiesel production, alkali catalyzed process and solid acid catalyzed process, are discussed with the help of Aspen Plus. By comparing some economic indicators, it can be found that solid acid catalysis could be a good choice for investors in the near future.